Perancangan Aplikasi Tebak Gambar Untuk Anak Tunarungu - Elistiana, Khoerotul Melina; Baihaqi, Wiga Maulana (Puslitbang Sinergis Asa Professional, 2023)
Indonesia is one of the countries with the largest population in the world so it has various community groups, one of which is children with special needs who are deaf. A deaf child is someone who has lost the ability to hear. At a school in Purwokerto, deaf students cannot recognize general knowledge and arelazy to learn, especially in flat shape material. Often children like this need special tools in their learning to be effective, but the price of a teaching aid is quite expensive, so not all schools can afford it. As the technology of teaching aids develops, an application system that is more practical can be made, users just need to install it, no need to incur costs. In order for everything to be achieved, an MDLC (Multimedia Development Life Cycle) method was applied which was developed by Luther. This method has several stages of research such as concept, design, material collection, assembly, testing and distribution. Where the results of the research contain application designs that suit the needs of deaf children with features that are easy to understand.